Synthesis and magnetic transitions of rare-earth-free Fe–Mn–Ni–Si-based compositionally complex alloys at bulk and nanoscale - Shabbir Tahir; Tatiana Smoliarova; Carlos Doñate-Buendía; Michael Farle; Natalia Shkodich; Bilal Gökce (Beilstein Journal of Nanotechnology)
Magnetic phase transitions at the Curie temperature are essential for applications like magnetocaloric refrigeration, magnetic sensors, and actuators, but the reliance on costly, scarce rare-earth materials limits sustainability. Developing affordable, rare-earth-free materials with tunable magnetic properties and scalable miniaturization methods is vital for advancing technology. We present a comprehensive synthesis approach for rare-earth-free compositionally complex alloys (CCAs) with magnetic phase transitions, spanning from bulk materials to nanoparticles. Specifically, we investigate Mn22.3Fe22.2Ni22.2Ge16.65Si16.65 (Ge-based CCA) and Mn0.5Fe0.5NiSi0.93Al0.07 (Al-based CCA). The bulk materials are prepared by ball milling and spark plasma sintering or powder pressing and sintering. Nanoparticles (NPs) from the bulk materials are synthesized by pulsed laser ablation in liquid. Magnetization measurements confirm a ferromagnetic-to-paramagnetic phase transition in bulk alloys, with Tc = 179 K for Ge-based CCA and Tc = 263 K for Al-based CCA. At the nanoscale, both Ge- and Al-based NPs exhibit superparamagnetic behaviour, with blocking temperatures of TB ≈ 120 K for Ge-based NPs (xc = 13.4 ± 15.5 nm, average particle size) and TB ≈ 100 K for Al-based NPs (xc = 18.4 ± 9.1 nm, average particle size), demonstrating the intrinsic superparamagnetic nature of NPs. While the Ge-based CCA demonstrates almost twice the saturation magnetization (Ms) and ≈20% lower hysteresis (Hc) in bulk form, the Al-based CCA exhibits comparable Ms and ≈45% lower Hc at the nanoscale at 5 K. These results indicate that the Al-based CCA is a promising, cost-effective alternative to Ge-based CCA at nanoscale, providing an economically viable and cost-effective alternative for nanoscale-based applications.